LEAD : leadership effectiveness in Africa and the African diaspora - Lituchy, Terri R.; Galperin, Bella L.; Punnett, Betty Jane (Palgrave Macmillan, 2017)
This book considers the new business environment of modern-day Africa, addressing how management styles must adapt to societal changes across the continent. As investment in the continent grows and African businesses begin to look beyond their own borders, there comes a real need to understand leadership from an Afro-centric perspective. This book explores the similarities and differences across African countries, compares them with other regions, and identifies particular cultural realities that managers must consider in order to be successful in the new business environment of modern Africa. Building on their Leadership Effectiveness in Africa and the African Diaspora (LEAD) research project, the authors provide an empirical understanding of African leadership styles and how businesses can harness these more effectively. Drawing on the African Diaspora's values, beliefs, and preferences, as well as anecdotal material from African academics and managers, this book grants a realistic view of leadership in various African countries including Egypt, Ghana, Nigeria, Kenya, Tanzania, Uganda, Ethiopia, and South Africa. It will be invaluable to academics, students, and anyone interested in African and global business leadership from a non-Western perspective.
Keywords: Leadership -- Africa.; Industrial management -- Africa.; Africa.; elektronické knihy; electronic books